2016
DOI: 10.1098/rspb.2015.2582
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen-related receptor α is required for transepithelial H + secretion in zebrafish

Abstract: Oestrogen-related receptor a (ERRa) is an orphan nuclear receptor which is important for adaptive metabolic responses under conditions of increased energy demand, such as cold, exercise and fasting. Importantly, metabolism under these conditions is usually accompanied by elevated production of organic acids, which may threaten the body acid-base status. Although ERRa is known to help regulate ion transport by the renal epithelia, its role in the transport of acid-base equivalents remains unknown. Here, we test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In zebrafish, several neuroendocrine factors are found to be involved in ionic and acid-base regulation during acid exposure, including cortisol [ 38 , 83 ], endothelin 1 [ 103 ], angiotensin II [ 104 ], stanniocalcin [ 49 , 105 ], catecholamines [ 106 ] and oestrogen-related receptor [ 107 ]. In other FW fish species, mRNA expression and/or plasma levels of thyroid hormone [ 108 ], prolactin [ 109 ], growth hormone [ 110 ] and somatolactin [ 110 , 111 ] are found to be modulated by acid exposure.…”
Section: Neuroendocrine Responses Following Acid Exposurementioning
confidence: 99%
See 3 more Smart Citations
“…In zebrafish, several neuroendocrine factors are found to be involved in ionic and acid-base regulation during acid exposure, including cortisol [ 38 , 83 ], endothelin 1 [ 103 ], angiotensin II [ 104 ], stanniocalcin [ 49 , 105 ], catecholamines [ 106 ] and oestrogen-related receptor [ 107 ]. In other FW fish species, mRNA expression and/or plasma levels of thyroid hormone [ 108 ], prolactin [ 109 ], growth hormone [ 110 ] and somatolactin [ 110 , 111 ] are found to be modulated by acid exposure.…”
Section: Neuroendocrine Responses Following Acid Exposurementioning
confidence: 99%
“…The oestrogen-related receptor (ERR) belongs to orphan nuclear receptors which control the transcription of several genes essential in energy metabolism in mammals [ 125 ]. In zebrafish, it was recently demonstrated that ERRa is involved in promoting acid secretion in zebrafish, partially by increasing the density of HRCs [ 107 ]. erra mRNA was found to be expressed in HRCs, and that acid exposure increased its abundance [ 107 ].…”
Section: Neuroendocrine Responses Following Acid Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, any biological system of interest should be studied with the minimum interference and under the most physiological condition possible. Such criteria are attained by the non-invasive ion-selective vibrating probe, which has been used for measuring multiple transmembrane ion fluxes in a wide variety of experimental systems, including Drosophila (Browne and O'Donnell, 2016), zebrafish (Guh et al, 2016), mouse skin (Sun et al, 2015), roots (He et al, 2015), Daphnia (Stensberg et al, 2014), C. elegans (Adlimoghaddam et al, 2014), etc. In pollen tubes, quantitative measurements of extracellular ion fluxes using the ion-selective vibrating probe have been fundamental in establishing the role of major ions (especially Ca 2+ , H + , K + , and anions) in apical growth.…”
mentioning
confidence: 99%